Cost-Volume-Profit (CVP) Analysis as a Profit Planning of Tour Packages at PT Tour East Indonesia, Denpasar - A A P R Dewi; C Ardina; A A P Suardani (Jurusan Akuntansi Politeknik Negeri Bali, 2018)
PT Tour East Indonesia is one of the companies engaged in travel agents in Bali. This company has not implemented a cost-volume-profit (CVP) analysis in preparing profit plans. This study aims to determine the level of tour package sales s at the level of break even, to determine the level of sales of tour packages that must be achieved in 2018 if the company wants a profit of 20% from 2017 and to analyze the level of margin of safety so that the company does not suffer losses in 2018. This study uses secondary data types. Data collection is done through interviews, documentation and observation. The analytical techniques used are descriptive quantitative analysis techniques including the least squares method to separate semi variable costs, contribution margin, break even point analysis, margin of safety analysis and profit planning analysis. The results of this study indicate that the analysis of cost-volume-profit (CVP) can help management in profit planning and also provide information on the break-even sales value of the tour package for 2018 amounting to Rp. 5.915.226.769 or 1.352 pax or 27% of sales budgeted in 2018. If the company wants to achieve a profit target of 20% of year profits 2017, then the tour package sales volume that must be achieved is Rp. 27.753.815.507. The level of security of the company's sales decline so as not to suffer losses in 2018 by 73%.